MEMAHAMI ISTI’ARAH DAN CONTOHNYA DALAM AL-QUR’AN - Fadilah Fitri Amaliah; Lili Suryani Siregar (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
As an authentic and perfect holy scripture, the Qur’an is naturally regarded as sacred and is often approached as a doctrinal text within a dogmatic-ideological framework. However, a methodological approach grounded in scientific and rational inquiry can provide greater intellectual satisfaction as well as deeper spiritual reassurance. In this context, the verses of the Qur’an especially those that contain ambiguous meanings (mutashabihat)require interpretation through an esoteric approach (ta’wil). The use of ta’wil opens up a wide range of interpretations, particularly in the study of the Qur’an’s language and literary aspects. This is essential, as the language of the Qur’an must be understood as guidance for humankind. One of the focal points in contemporary scholarship is the discourse on figurative language (metaphor) and literal meaning (denotative). At this point, reasoning plays a crucial role in achieving a deeper understanding of the Qur’anic verses. Although this approach is not universally accepted among all scholars, it has developed into a distinct field within Qur’anic exegesis and studies, commonly referred to as the concepts of haqiqa (literal meaning) and majaz (figurative expression).